2010
DOI: 10.1021/np100185a
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Anti-inflammatory Diterpenoids from the Soft Coral Sinularia gyrosa

Abstract: Chemical investigation of the soft coral Sinularia gyrosa led to the purification of three new diterpenoids, designated as gyrosanols A-C (1-3). The structures of 1-3 were elucidated through extensive spectroscopic analyses. Compounds 1 and 2 exhibited antiviral activity against HCMV with IC(50)'s of 2.6 and 3.7 microM, respectively. In addition, compounds 1 and 2 showed significant anti-inflammatory activity by reducing the levels of the COX-2 protein (19.6 + or - 3.9% and 29.1 + or - 9.6%, respectively) in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 23 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…Previous studies have indicated that diterpenes, a main constituent of the genus Sinularia , exhibit various biological activities, such as anti-inflammatory (Chao et al 2011; Cheng et al 2010; Lu et al 2010; Su and Wen 2011), antiviral (Cheng et al 2010), and cytotoxic (Grote et al 2008; Kamel et al 2007; Lo et al 2009; Su et al 2009) effects. As a part of our ongoing investigations on screening active compounds from Vietnamese Sinularia soft corals towards anti-inflammatory effects (Thao et al 2012, 2013a, b), we recently reported the isolation, structure elucidation, and inhibitory effects on lipopolysaccharide-stimulated production of proinflammatory cytokines in bone marrow-derived dendritic cells of 12 diterpenoids [sinumaximol A ( 1 ), sinumaximol B ( 2 ), sinumaximol C ( 3 ), sethukarailin ( 4 ), sinumaximol D ( 5 ), sinumaximol E ( 6 ), sinumaximol F ( 7 ), sinumaximol G ( 8 ), sinumaximol H ( 9 ), (1 S ,2 E ,4 S ,6 E ,8 S ,11 R )-2,6,12(20)-cembratriene-4,8,11-triol ( 10 ), isomandapamate ( 11 ), and sinumaximol I ( 12 )] (Thao et al 2012) and 7 norditerpenoids [scabrolide A ( 13 ), 12-hydroxy-scabrolide A ( 14 ), yonarolide ( 15 ), ineleganolide ( 16 ), 5-epinorcembrene ( 17 ), 13- epi -scabrolide C ( 18 ), and norcembrene 5 ( 19 )] (Thao et al 2013a) from Sinularia maxima (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that diterpenes, a main constituent of the genus Sinularia , exhibit various biological activities, such as anti-inflammatory (Chao et al 2011; Cheng et al 2010; Lu et al 2010; Su and Wen 2011), antiviral (Cheng et al 2010), and cytotoxic (Grote et al 2008; Kamel et al 2007; Lo et al 2009; Su et al 2009) effects. As a part of our ongoing investigations on screening active compounds from Vietnamese Sinularia soft corals towards anti-inflammatory effects (Thao et al 2012, 2013a, b), we recently reported the isolation, structure elucidation, and inhibitory effects on lipopolysaccharide-stimulated production of proinflammatory cytokines in bone marrow-derived dendritic cells of 12 diterpenoids [sinumaximol A ( 1 ), sinumaximol B ( 2 ), sinumaximol C ( 3 ), sethukarailin ( 4 ), sinumaximol D ( 5 ), sinumaximol E ( 6 ), sinumaximol F ( 7 ), sinumaximol G ( 8 ), sinumaximol H ( 9 ), (1 S ,2 E ,4 S ,6 E ,8 S ,11 R )-2,6,12(20)-cembratriene-4,8,11-triol ( 10 ), isomandapamate ( 11 ), and sinumaximol I ( 12 )] (Thao et al 2012) and 7 norditerpenoids [scabrolide A ( 13 ), 12-hydroxy-scabrolide A ( 14 ), yonarolide ( 15 ), ineleganolide ( 16 ), 5-epinorcembrene ( 17 ), 13- epi -scabrolide C ( 18 ), and norcembrene 5 ( 19 )] (Thao et al 2013a) from Sinularia maxima (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Cell Western blot analysis. Cells were treated with 0, 5, 20 and 80 µmol/l PAB solution for 24 h. The cells were then harvested (cell number, >5x10 6 /ml) and washed twice with cold PBS. Western blot analysis was performed.…”
Section: Assessment Of Morphological Changes A549 Cells (50x10mentioning
confidence: 99%
“…Diterpene acid is one of the numerous traditional Chinese medicines that has a long history of recordation and clinical application (5). Diterpene acid has antiviral, anti-inflammatory, antitumor, antifungal and immunosuppressive effects (6)(7)(8)(9). Pseudolaric acid B (PAB; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The genera of Sinularia and Lobophytum (Phylum: Coelenterata, Family: Alcyoniidae, Class: Anthozoa, Order: Alcyonacea) are two of the most widely distributed of their genera, constituting a dominant portion of the biomass in tropical reef environments (Anjaneyulu and Rao, 1997;Lakshmi and Kumar, 2009). Previous studies have indicated that diterpenes, a main constituent of the genus Sinularia and Lobophytum (most are derived from the 14-membered cembrane nucleus), exhibit various biological activities, such as anti-inflammatory (Chao et al, 2011;Cheng et al, 2010;Lu et al, 2010;Su and Wen, 2011), antiviral (Cheng et al, 2010), and cytotoxic (Grote et al, 2008;Kamel et al, 2007;Lo et al, 2009;Su et al, 2009) effects.…”
Section: Introductionmentioning
confidence: 99%